The innovation path of the Chinese wind power industry - Yixin Dai; Di Xia; Yuan Zhou; Lan Xue (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
The Chinese wind energy sector has undergone rapid development over the past 30 years, yet its path has differed from that of its European counterparts. There is much discussion in the literature on what the path of innovation is for the Chinese wind energy sector and where this path will lead. This research contributes to the literature by attempting to answer three questions: What is the technological path of innovation in China's wind sector? How did this path of innovation emerge? What are the determinants of this path? To fully understand the Chinese wind energy innovation path, this research first summarises the history of the development of wind energy technology from the perspectives of both core technology innovation and deployment technology. The core technology innovation involved a change in strategy from preferring lower prices to preferring higher quality, from small-turbine to large-turbine technology and from imported technology to indigenous technology, while wind energy deployment experienced a path change from a centralised deployment pattern with a partial production chain to a de-centralised pattern with a whole-production-chain strategy. Against these background features, this paper presents three individual cases of a wind turbine producer, a wind farm and a wind blade producer to illustrate how foreign collaboration and technology, choice of deployment strategy, and government policy have influenced the sector to continually improve its technology. The findings indicate that foreign technology and collaboration have had a significant role in helping wind energy technology to develop in China, and were also key elements in stimulating indigenous innovation when high prices held the domestic wind market back from massive expansion. While public policy has played a key role in many aspects of the development of the innovation path, the long-term, enduring goal of developing the required technology was the essential driver. The development of the wind sector occurred alongside the economic development and social improvement of the nation. Thus, while it may be too soon to predict the future path of innovation for Chinese wind energy technology, an emphasis on research and development and increasing international competition is a trend that is likely to continue.
Keywords: 330; Energie; Technology and innovation